Transverse momentum distributions of charmonium states with the statistical hadronization model - Andronic, Anton; Braun-Munzinger, Peter; Köhler, Markus Konrad; Stachel, Johanna (Physics letters, 2019)
Calculations and predictions are presented within the framework of the statistical hadronization model for transverse momentum spectra of the charmonium states J/ψ, ψ(2S) and X(3872) produced in nucleus-nucleus collisions at LHC energies. The results are confronted with available data and exhibit very good agreement by using particle flow profiles from state-of-the-art hydrodynamic calculations. For X(3872) production in Pb-Pb collisions we predict a transverse momentum distribution similar in shape to that for J/ψ with a strong enhancement at low transverse momenta and a production yield of about 1% relative to that for J/ψ.
Gesehen am 24.10.2019